Synthesis And Characterization Of Zno, V2O5 And Mno2 Nanostructures Photocatalysts On Polyetylene Terephthalate (Pet) Fiber For Degradation Of Rhb Dye - Chan, Yim Leng (2014)
Increasing pollution into the water system particularly from textile industries and agriculture has become a source of health concern across the globe. Advanced oxidation process is a rapid developing research field for the application in degradation of organic the semiconductor's surface in the presence of UV or visible light irradiation. In order to utilize sunlight effectively for organic pollutants removal, the photocatalytic activities of wide bandgap semiconductor (ZnO. Eg =3.37 eV) and narrow bandgap semiconductors (MnO2. Eg = 1.00 to I.<30 eV and polymorphs of MnO2 nanoparticles were synthesized using hydrothermal method by adjusting the ratio of KM11O4 and MnSO4. The photodegradation of RhB solution by these semiconductor nanoparticles followed first order kinetic. Under UV irradiation. ZnO has good photodegradation efficiency (0.034 min'1). On the other hand. V2O.s nanorods and p- MnO2 nanoparticles degraded RhB dye under visible light with rate constant of 0.01 5 min'1 and 0.022 min'1 respectively. A relined photodegradation model of RhB solution by these semiconductor photocatalysts is proposed. Two processes, i.e. N-deethylation and cycloreversion happen simultaneously during the photodegradation of RhB solution.